A Multi-State Rotational Control Strategy for Hydrogen Production Systems Based on Hybrid Electrolyzers - Qingshan Tan; Ke Li; Longquan Zeng; Lu Xie; Man Cheng; Wei He (Energies)
Harnessing surplus wind and solar energy for water electrolysis boosts the efficiency of renewable energy utilization and supports the development of a low-carbon energy framework. However, the intermittent and unpredictable nature of wind and solar power generation poses significant challenges to the dynamic stability and hydrogen production efficiency of electrolyzers. This study introduces a multi-state rotational control strategy for a hybrid electrolyzer system designed to produce hydrogen. Through a detailed examination of the interplay between electrolyzer power and efficiency—along with operational factors such as load range and startup/shutdown times—six distinct operational states are categorized under three modes. Taking into account the differing dynamic response characteristics of proton exchange membrane electrolyzers (PEMEL) and alkaline electrolyzers (AEL), a power-matching mechanism is developed to optimize the performance of these two electrolyzer types under varied and complex conditions. This mechanism facilitates coordinated scheduling and seamless transitions between operational states within the hybrid system. Simulation results demonstrate that, compared to the traditional sequential startup and shutdown approach, the proposed strategy increases hydrogen production by 10.73% for the same input power. Moreover, it reduces the standard deviation and coefficient of variation in operating duration under rated conditions by 27.71 min and 47.04, respectively, thereby enhancing both hydrogen production efficiency and the dynamic operational stability of the electrolyzer cluster.